Respon Fisiologi Pasak Bumi (Eurycoma longifolia, Jack) di Bawah Cekaman Kekeringan - Zulfahmi, Zulfahmi; Irnanda, Eko; Gusrinaldi, Gusrinaldi; Elfianis, Rita; Rosmaina, Rosmaina (Universitas Sebelas Maret, 2025)
Drought stress is one of the abiotic factors that can inhibit plant growth and yield. This study aims to assess the effect of drought stress on the physiological characteristics of pasak bumi (Eurycoma longifolia, Jack). This study used a completely randomized design with two treatments, namely P0 = daily watering (control) and P1 = drought stress for two days. Each treatment consisted of 15 plants; there were 30 sample plants. Parameters observed included chlorophyll content, stomatal conductance, transpiration rate, photosynthetic rate, and Water Use Efficiency. The results of this study showed that drought stress decreased chlorophyll content (5.81%), stomatal conductance (10.34%), transpiration rate (18.73%), photosynthetic rate (3.78%), and water use efficiency (33.127%) compared to control plants. Eurycoma longifolia Jack exhibits an adaptive physiological response to drought stress, characterized by moderate reductions in chlorophyll content, photosynthesis rate, and stomatal conductance while maintaining efficient photosynthetic activity. Although water use efficiency declined significantly, the findings indicate effective compensatory mechanisms, positioning this species as a potential candidate for cultivation under water-limited conditions.